The Orc Diary - Calderón Mendoza, José Juan (2024)
It is a journey through the life of an orc of Middle-earth from his birth (during the Third Age, at the time of the War of the Ring) to his arrival on the battlefield in Mordor. His journey across territories and situations strengthens his temper and his own vision of the world where he lives, alongside other orcs, and where he gets to know important characters from Tolkien’s cosmogony. It is a glimpse into the origins, customs, and motives of this despised, despicable, but also sorrowful race.